Предмет: Алгебра,
автор: 123540987
помогите решить систему
(х-2)(у-1)=36
х-2у=6
Ответы
Автор ответа:
0
Найдем х из второго и подставим в 1
х=2у+6
(2у+6-2)(у-1)=36
(2у+4)(у-1)=36
2у²-2у+4у-4-36=0
2у²+2у-40=0
у²+у-20=0
у1+у2=-1 и у1*у2=-20⇒у1=-5 и у2=4
х1=2*(-5)+6=-10+6=-4 и х2=2*4+6=8+6=14
ответ(-4;-5) и (14;4)
х=2у+6
(2у+6-2)(у-1)=36
(2у+4)(у-1)=36
2у²-2у+4у-4-36=0
2у²+2у-40=0
у²+у-20=0
у1+у2=-1 и у1*у2=-20⇒у1=-5 и у2=4
х1=2*(-5)+6=-10+6=-4 и х2=2*4+6=8+6=14
ответ(-4;-5) и (14;4)
Автор ответа:
0
Спасибо!
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: dansakovich
Предмет: География,
автор: lera2008pavlova
Предмет: Физика,
автор: googlemen76